The effect of surface treatments on the shear bond strength of acrylic resin denture base with different repair acrylic resin: An in vitro study - P Arun Kumar; K Iniyan; R Balasubramaniam; M Viswanathan; P Allen Jim Hines; V Monnica (Wolters Kluwer Medknow Publications, 2019)
Background: Fracture of the denture base is a common problem associated with dental prostheses. Fractured denture base surfaces treated with chemical agents and mechanical features have the potential for improved bond strength. Aim: The aim of this study was to evaluate the effect of surface treatment on the shear bond strength of heat-cured denture base with different repair acrylic resins. Materials and Methods: A total of 100 circular specimens (2-cm diameter × 3.3-mm thickness) were fabricated from heat-cured denture resins (DPI) according to the manufacturer's instructions. The heat-cured denture base acrylic resin specimens were divided into two groups: In group 1, auto-polymerizing acrylic resin (DPI) was used as a repair resin, and in group 2, light-cured acrylic resin (VLC) was used as the repair resin. Further, the heat-cured denture base acrylic resin specimens were subdivided into five subgroups. The shear bond strength (in megapascal) was measured in a universal testing machine at a crosshead speed of 1mm/min. The results were subjected for statistical analysis. Result: Comparison of mean and standard deviation of shear bond strength between DPI and VLC group using one-way analysis of variance showed that the mean shear bond strength of DPI group is higher than that of VLC group. Conclusion: From the study, heat-cured denture base specimens repaired with auto-polymerizing repair resin showed higher mean shear bond strength than the visible light cure resin material.